Social marketing for digital transformation: digitalizing social action for the development of women at risk of exclusion - Rivera, Reynaldo Gustavo (2020)
The third sector, key to social and personal development, needs to evolve and adapt to the technological revolution and digitalization that accelerated due to the global pandemic of COVID-19. Social marketing offers strategies and tools that allow digitalizing processes of female empowerment in contexts of poverty, violence, inequality, and social exclusion. People living in these contexts were the ones that suffered the most from the pandemic, both due to the number of deaths coupled with a lack of access to quality health care, and an increase in interpersonal conflict. The latter aggravated by the mandatory isolation measures imposed by the governments, which made it practically impossible for civil society organizations (CSOs) to intervene. This article presents a case of social marketing oriented to the development, implementation, and evaluation of a people-centered protocol (EduQualitas SM) for the digitalization of empowerment and positive personal development, based on interpersonal relationships and reflexiveness. Through qualitative and quantitative methodologies, the study analyses the impact of its application in a social marketing campaign (Orientación Familiar Digital - OFD) that aimed to improve the quality of life of women in the area of ​​greatest social exclusion in Argentina. The implemented campaign sought to digitalize the formative processes of an international CSO and develop empathy, a fundamental capacity for the quality of life and the reduction of both structural poverty and violence against women. The impact assessment of EduQualitas SM was of a mixed design that included a quasi-experimental intervention without a control group, based on the Argentine adaptation of the Interpersonal Reactivity Index (IRI). This research presents one of the first Latin American cases of CSO digitalization strategies for the development of empathy of women in situations of social exclusion.